Historical view of the effects of radiation on cancer cells - Hazout, Saskia; Oehler, Christoph; Zwahlen, Daniel R.; Taussky, Daniel (Oncology Reviews, 2025)
IntroductionSince Röntgen’s discovery of X-rays in 1895, advancements in radiobiology have significantly shaped radiotherapy practices. This historical review traces the evolution of radiobiological theories and their impacts on current therapeutic strategies.Materials and MethodsDatabases such as PubMed were utilized to trace the evolution of concepts in radiobiology.Results/DiscussionOne of the first theories concerning the effect of radiation was Dessauer’s target theory, introduced in the 1920s. He found that damage to critical molecular cellular targets leads to cell death. In the early 20th century, Muller contributed to the understanding of DNA structure and radiation-induced mutations, highlighting theories on the impact of radiation on genetic material and cellular damage. In 1972, Kellerer and Rossi introduced the theory of dual radiation action, which explains that ionizing radiation induces sequential damage to DNA, starting with single-strand breaks and progressing to irreparable double-strand breaks. Recent advances have enhanced the understanding of the effects of radiation on the microenvironment and immune responses, thereby improving therapeutic outcomes. The significance of the sigmoid dose–response curve and the initial shoulder effect were recognized early, leading to theoretical models such as the multitarget single-hit, linear-quadratic and repair-misrepair models. The history of fractionation and the 4R/5R principles have informed today’s ultrahigh fractionation techniques, including single doses of approximately 20 Gy.ConclusionAlthough significant advances have been made toward understanding the effects of radiation on cancerous and healthy tissues, many clinical observations, such as the effects of very high doses or FLASH therapy, remain poorly understood.